Impact of fair value measurement challenges in biological assets on accounting information quality perspectives of auditors - Jayawardana, W.M.S.S.; Herath, M.N.; Munasinghe, M.A.T.K. (University of Jaffna, 2022)
Purpose: Sri Lanka's agricultural sector is the country's primary driver of GDP growth. Financial data can lead to growth and development decisions in the agricultural sector. However, the impact of valuation methods on these decisions is unspecified. This study uses fair value valuation, as recommended by SLFRS 13 and LKAS 41, to assess biological assets. The purpose of this research is to get insight from auditors' perspectives on the difficulties of assigning a fair value to biological assets. Methodology: Data were collected using a Likert Scale Questionnaire from auditors who are engaged with the agriculture sector audits. The population of the study consists with external auditors and internal auditors who engage with the agriculture sector audits in Sri Lanka. The sample was the external and internal auditors including audit seniors, audit managers and the partners of the audit firms those who have experience in the auditing of the agriculture sector companies. Descriptive and inferential statistics, as well as the independent sample t-test, were used to a data set consisting of 151 replies. Findings: The study's results suggest that there is a significant difference between auditors' perception of the challenges in fair value measurement of biological assets arise when using level 2 inputs defined in SLFRS 13. And also there is no any significant difference between the responses of Challenges in fair value measurement by level 3 inputs. Further, there is no statistically significant differences between Impact on relevance and reliability of Accounting Information arise when using fair value method for biological assets valuation. Research limitations: Due to the workloads and tight schedules of auditors of agriculture companies in Sri Lanka, it was difficult to collect higher number of responses to this study and this research doesn't consider the perception of parties of other accounting professional regarding the challenges of fair value measurement of biological assets. Implications: The findings of the study provide practical implications, for the parties to the accounting profession. Mainly the finance managers, accountants, assistant accountants of the company could get an understanding of the perception of auditors on the challenges in fair value measurement of biological assets and their impact on accounting information. In addition, the research would give insights for other users of information in agriculture sector to identify about the fair valuation challenges in the agriculture sector and their influence on financial information of the agriculture firms.
Keywords: Auditors' perception; Biological assets; Challenges; Fair value measurement; Financial information